Gender pay Gap in education sector in Azerbaijan - Karimova, Sezen (ADA University, 2020)
Today, women make up very big proportion the labor workforce in the education sector in Azerbaijan, however they continue to earn less than men. Little research has been done on the Azerbaijan labor market, so the primary goal of this research is the measurement of the gender pay gap, identification of the key determinants of the gender wage discrimination in Azerbaijan and its consequences on the society and labor force. This study attempts to measure wage discrimination by looking directly at pay disparity between men and women in the same jobs and personal characteristics and by contrasting wage to specific productivity measures. The quantitative research method was implemented based on the survey format addressing teachers, instructors, professors and deans of six universities, colleges and schools in total. The female-to male earnings ratio, based on the median earnings of 81 men and 152 women from survey is 0.53, and the total gender raw wage gap is 872.3 AZN in numbers or 87%. Women are doing the same jobs as men and have higher human capital characteristics, but gap still persists. After controlling for the productivity variables in the Blinder-Oaxaca wage decomposition, it is estimated that only 12% of the gap is explained by the self-explanatory characteristics. The wage gap persists due to a variety of factors including social and religious norms as the unconscious bias of employers, leading to significant lost wages, benefits and career opportunities , which contribute towards persistent gender inequality and impedes economic growth. Traditions and gender roles can impact the occupational segregation of women , their educational choice and the selection and promotion management of the HR management in organizations (European Commission report, 2013). As religion is strongly overlapped with social norms and values, we measured that 17% of the gender wage gap is explained by the combination of religiousness and the conservative or patriarchic type of society of the respondents, and we face gender wage discrimination on the both groups of patriarchic male female and religious male female groups. But no discrimination is observed on religious or patriarchic women within the pool of all female employees. Moreover, flexible job arrangement of teachers’ work doesn’t cause the gender wage discrimination towards women but rather positively contributes the work-life balance and maternity obligations of female workers. These studies consistently find evidence of ongoing labor market discrimination and support the findings that women are still facing differential on the-job treatment Indeed, achieving gender pay equity is critical for the employee retention and satisfaction, but challenging and long process requiring strong commitment.
Keywords: Business; Women -- Employment.; Women -- Employment -- Education.; Equal pay for equal work.; Women -- Education.; Income distribution -- Azerbaijan.